Occurrence, heat and antibiotic resistance profile of Bacillus cereus isolated from raw cow and processed milk in Mezam Division, Cameroon. (29th March 2016) - Tatsinkou Fossi, Bertrand; Tatah Kihla Akoachere, Jane‐Francis; Nchanji, Gordon Takop; Wanji, Samuel
Abstract : Bacillus cereus is the aetiologic agent of two distinct forms of food poisoning: the diarrhoeal and emetic syndromes. Little data exist on the prevalence of B. cereus in raw milk and milk products sold in Cameroonian towns. This study was aimed at investigating the occurrence, heat and antibiotic resistance of B. cereus isolated from raw milk and selected milk products in Mezam division, Cameroon . Bacillus cereus was isolated by inoculating samples onto mannitol‐egg yolk‐polymyxin B agar. Isolates were characterised morphologically and biochemically. The occurrence of B. cereus in raw milk (8.22%) was less than that in milk powder (13.33%). Bacillus cereus was not isolated from fermented milk. There was no significant difference ( P < 0.05) between the B. cereus load in raw milk (2.6 × 10 3 cfu/mL) and milk powder (3.0 × 10 2 cfu/mL). All the isolates showed haemolysin activity and were sensitive to tetracycline, gentamicin, chloramphenicol and nalidixic acid, but resistant to penicillin, ampicillin and trimethoprim/sulphamethoxazole. The detection of drug‐resistant, haemolysin‐positive isolates should serve as a warning for an impending health hazard following consumption of untreated milk. Heat resistance of isolates was assessed by determining the decimal reduction time; D ‐value (time to inactivate 90% of the B. cereus spores); and the heat sensitivity, z (temperature increase leads to a tenfold reduction in the D ‐value). The values for D 100 ranged from 0.5 to 3.5 min, and z ‐values ranged from 10.0 to 32.6 °C. These results could be used in the dairy industry to evaluate the importance of heat treatment on B. cereus inactivation and calculation of process efficiency.